Stable bismuth-antimony alloy cathode with a conversion-dissolution/deposition mechanism for high-performance zinc batteries. (December 2021) - Zhao, Yuwei; Jiang, Feng; Hong, Hu; Wang, Donghong; Li, Qing; Meng, You; Huang, Zhaodong; Guo, Ying; Li, Xinliang; Chen, Ao; Zhang, Rong; Zhang, Shaoce; et al.
Graphical abstract: Abstract: Although a large number of intercalation cathode materials for aqueous Zn batteries have been reported, limited intercalation capacity precludes achieving a higher energy density. Here we develop a high-performance aqueous Zn battery based on BiSb alloy (Bi0.5 Sb0.5 ) using a high-concentrated strong-basic polyelectrolyte. We demonstrate that a conversion-dissolution/deposition electrochemical mechanism (BiSb ↔ Bi + SbO2 −  ↔ Bi + SbO3 −  ↔ Bi2 O3 ) through in situ X-ray diffraction (XRD), Raman, and ex-situ X-ray photoelectron spectrometry (XPS) characterizations with the help of density functional theory calculations. The BiSb cathode delivers large capacity of 512 mAh g −1 at 0.3 Ag −1 and superior rate capability of 90 mAh g −1 even at 20 Ag −1, and long-term cyclability with capacity retentions of 184 mAh g −1 after 600 cycles at 0.5 Ag −1 and 130 mAh g −1 after 1300 cycles at 1 Ag −1 . Remarkably, even at temperatures as low as −10 and −20 °C, capacities of 210 and 197 mAh g −1 are reserved at 1 Ag −1, respectively. Moreover, the prepared pouch Zn//BiSb battery delivers a high energy density of 303 Wh kg −1 BiSb at 0.3 Ag −1 . When coupled with a high concentration polyelectrolyte, the Zn/BiSb battery exhibits an excellent performance over a wide temperature range (−40 to 40 °C). Our research reveals the metal cathode is promising for Zn batteries to achieve a high performance with the unique mechanism and alloys can be an effective approach to stabilize metal electrodes for cycling.